Spatiotemporal variation in the adult sex ratio, male aggregation, and movement of two tropical cloud forest dung beetles. Issue 6 (25th December 2021) - Barretto, Julliana; Baena, Martha L; Domínguez, Israel Huesca; Escobar, Federico
Abstract: While theory suggests that at conception the sex ratio should be balanced (1:1), this can be variable across space and time in wild populations. Currently, studies of the environmental factors that regulate adult sex ratio (ASR) in species with different life history traits are scarce. Using capture–recapture over a year, we analyzed the influence of habitat type (forest and nonforest) and season (rainy and dry) on variation in ASR, male aggregation and the trajectory movement of 2 dung beetle species with different life history traits: Deltochilum mexicanum (a hornless roller species) and Dichotomius satanas (a tunneler species with horns on its head and thorax). We found opposite tendencies. The D. mexicanum population tends to be female-biased, but the population of D. satanas tends to be predominantly male, and observed values were not related to habitat type or season. However, the 95% confidence intervals estimated were highly variable between seasons depending on habitat. On examining the monthly variation in ASR for both habitats, we found that it depends on the species. In addition, male aggregation differed between species depending on habitat type and season, and species movement patterns were closely related to their habitat preferences. Based on our results, we argue that comparative population studies of species with different life history traits are necessary to understand the variation in demographic parameters as well as its ecological and evolutionary implications in the face of spatial and climatic environmental variation.